Trends in the Incidence of Clavicle Fractures and Surgical Repair in Sweden: 2001-2012 - Huttunen, Tuomas T; Launonen, Antti P; Berg, Hans E; Lepola, Vesa; Felländer-Tsai, Li; Mattila, Ville M (Journal of bone and joint surgery. American volume, 2016)
Clavicle fractures are common injuries causing substantial morbidity. Recent literature suggests that the incidence of surgically treated clavicle fractures has increased. However, it is unknown whether the increase is caused by more surgeons choosing operative over nonoperative treatment for the injury or an increase in the actual incidence of clavicle fractures. The aim of this study was to assess both the national incidence of clavicle fractures and the rate of surgical treatment of those fractures in Sweden. We assessed the incidence and trends of clavicle fractures and rates of surgery in Sweden. The validated Swedish Hospital Discharge Register offers a unique opportunity to assess both outpatient and inpatient visits and was used to conduct a national register-based study including all adults (≥18 years of age) with a diagnosis of clavicle fracture in Sweden between 2001 and 2012. A total of 44,609 clavicle fractures occurred in Sweden between 2001 and 2012. The incidence of clavicle fractures increased from 35.6 per 100,000 person-years in 2001 to 59.3 per 100,000 person-years in 2012. Interestingly, the highest incidence rates were observed in the oldest age groups. The increase in the rate of surgically treated clavicle fractures (705%) was greater than the increase in the actual fracture incidence (67%). Most (77%) of the surgically treated patients were men. Open reduction and plate fixation was the most common surgical procedure. Overall, the proportion of surgically treated clavicle fractures increased markedly. Although the incidence of clavicle fractures increased in Sweden between 2001 and 2012, the rate of surgical treatment of clavicle fractures increased much more than could be expected solely based on the increase in the fracture incidence. The observed changes in the rates of surgery require additional studies since there is still controversy regarding the indications for surgical treatment.